Improving fluid balance monitoring on the wards. Issue 1 (18th November 2015) - Jeyapala, Sobanakumari; Gerth, Alice; Patel, Aarti; Syed, Nazia
Abstract: Clinical experience and nursing metrics have consistently identified poor documentation of fluid balance monitoring at Milton Keynes University Hospital, compromising patient safety and quality of care. This project aimed to increase the percentage of fluid balance charts correctly completed on the wards. Three areas for improvement were identified: understanding the importance of good fluid balance monitoring, correct identification of patients requiring monitoring, and ease of completion of fluid balance charts. Three interventions were deployed on two acute medical awards in consecutive cycles; 1) small group education for staff, 2) creation of board magnets to aid the multidisciplinary team to identify patients requiring monitoring, 3) modification of the current fluid balance chart. Questionnaires were utilised to highlight improvements with current charts and measured staff awareness pre and post education. Each intervention was implemented for one week followed by daily surveys for four days to monitor compliance. Initial results showed a range of 6-12 charts used daily per ward. Of these 0-45% of them were correctly filled. Post education there was a reduced number of inappropriate charts. Introduction of board magnets improved correlation between doctors and nurses in identification of patients (52% before, 77% after magnets). Following modification there was a subjective improvement in the quality of chart completion. This study highlighted that understanding and use of fluid balance monitoring can be improved for nurses, health care assistants (HCAs), and doctors. These improvements allow better documentation and safer patient care. As a result, Milton Keynes University Hospital is investing in magnets and modified charts for a Trust-wide pilot.